N,N′-Bis(2-cyclohexylethyl)naphtho[2,3-b:6,7-b′]dithiophene Diimides: Effects of Substituents - Masahiro Nakano; Daisuke Hashizume; Kazuo Takimiya (Molecules, 2016)
Naphtho[2,3-b:6,7-b′]dithiophene-4,5,9,10-tetracarboxylic diimide (NDTI) is a promising electron-deficient building block for n-type organic conductors, and the performance of NDTI-based field-effect transistors (FETs) is largely dependent on the substituents that alter the supramolecular organization in the solid state and, in turn, the intermolecular orbital overlap. For this reason, the rational selection of substituent on imide nitrogen atoms and/or thiophene α-positions is the key to developing superior n-type organic semiconductors. We here report new NDTI derivatives having N-(2-cyclohexylethyl) groups. Despite their one-dimensional packing structures in the solid state regardless of the presence or absence of chlorine groups at the thiophene α-positions, their FETs show promising performance with electron mobilities higher than 0.1 cm2·V−1·s−1 under ambient conditions. We also discuss how the cyclohexylethyl groups affect the packing structure in comparison with analogous n-octyl derivatives having the same number of carbon atoms.